Dynamical (harmonic) interface stress field in the half-plane covered by the prestretched layer under a strip load - Akbarov, SD; Guler, C (SAGE PUBLICATIONS LTD, 2005)
Within the framework of the piecewise homogeneous body model, by employing the three-dimensional linearized theory of elastic waves in initially stressed bodies the dynamical problem of the stress distribution in a half-plane covered with a prestretched layer is investigated. It is assumed that the free face plane of the covered layer is subjected to a uniformly distributed harmonic load acting on a strip extending to infinity in the x(3) direction, which is perpendicular to the x(1)-x(2) plane and is of width 2a in the x, direction. The plane-strain state in the x(1)-x(2) plane is analysed. The corresponding boundary-value problems are investigated by employing the exponential Fourier integral transformation. The numerical results regarding the interface normal stress distribution are presented. The influences of the problem parameters and pre-stretching of the covered layer on this distribution are analysed. Practical engineering application fields of the results are suggested.
Keywords: prestretching; layer; half-plane; dynamical stresses; harmonic loading; GROUND VIBRATION; RECTANGULAR LOAD; VICINITY; SPACE; Engineering; Mechanics; Materials Science